Neuromyelitis Optica in Austria in 2011: To Bridge the Gap between Neuroepidemiological Research and Practice in a Study Population of 8.4 Million People - Aboul-Enein, Fahmy; Seifert-Held, Thomas; Mader, Simone; Kuenz, Bettina; Lutterotti, Andreas; Rauschka, Helmut; Rommer, Paulus; Leutmezer, Fritz; Vass, Karl; Flamm-Horak, Agathe; Stepansky, Robert; Lang, Wilfried; et al. (PLOS ONE, 2013)
BackgroundIn 2008 the Austrian Task Force for Neuromyelitis Optica (NMO) started a nation-wide network for information exchange and multi-centre collaboration. Their aim was to detect all patients with NMO or NMO spectrum disorders (NMO-SD) in Austria and to analyse their disease courses and response to treatment. Methods(1) As of March 2008, 1957 serum samples (of 1557 patients) have been tested with an established cell based immunofluorescence aquaporin-4 antibody (AQP4-ab) assay with a high sensitivity and specificity (both >95%). All tests were performed in a single reference laboratory (Clinical Dept. of Neurology of the Innsbruck Medical University). (2) A nation-wide survey with several calls for participation (via email newsletters, articles in the official journal of the Austrian Society of Neurology, and workshops) was initiated in 2008. All collected data will be presented in a way that allows that every individual patient can be traced back in order to ensure transparency and to avoid any data distortion in future meta-analyses. The careful and detailed presentation allows the visualization and comparison of the different disease courses in real time span. Failure and response to treatment are made visible at one glance. Database closure was 31 December 2011. All co-operators were offered co-authorship. ResultsAll 71 NMO- or NMO-SD patients with AQP4-ab positivity (age range 12.3 to 79.6 years) were analysed in detail. Sex ratio (m:f = 1:7) and the proportion of patients without oligoclonal bands in cerebrospinal fluid (86.6%) were in line with previously published results. All identified patients were Caucasians. ConclusionsA nationwide collaboration amongst Austrian neurologists with good network communications made it possible to establish a database of 71 AQP4-ab positive patients with NMO/NMO-SD. This database is presented in detail and provides the basis for further studies and international cooperation in order to investigate this rare disease.